Modification of Oligopeptides on Aspartic Acid or Lysine Residues by Solid-Phase Synthesis through On-Resin Side-Chain Conjugation - Ning, Xibo; Liu, Di; Liu, Shimiao; Zhang, Mingjie; Shen, Hongyan (Synlett, 2018)
On-resin side-chain conjugations of various moieties to oligopeptides were performed through an orthogonal protecting protocol using side-chain-protecting groups for aspartic acid or lysine that could be selectively removed on-resin. Various types of modification, such as PEGylation, biotinylation, glycosylation, or fluorophore-labeling of peptides, were realized by using this strategy. The formation of ester, amide, hydrazide, and thiourea bonds was accomplished through the on-resin conjugation. Our work provides an improved and convenient solid-phase synthetic protocol for the modification of oligopeptides on their aspartic acid or lysine residues. This is a universal and practical method that is expected to increase the potential application of peptide-related drugs.
Keywords: oligopeptides; solid-phase synthesis; protecting group; PEGylation; biotinylation; glycosylation